"Weekend" as a symbolic sign in motivational counseling sessions in the probation service with substance abusers. (July 2016) - Sarpavaara, Harri
This study explores the meanings that substance-abusing clients attach to weekend during motivational counseling sessions in Finnish Probation Service. By applying Peirce's semiotic theory of signs, this article studies "weekend" as a symbolic sign, and analyzes: (a) What kind of meanings the clients attach to it? (b) What does weekend mean to the clients' motivation to change? The analyses are based on videotaped and transcribed data consisting of 98 motivational counseling sessions. The results of the study display that the general meaning of weekend is constructed as an obstacle to change. Weekend stands for an excuse to drink, a need to drink, a desire to drink and incapability to change in the clients' talk. The results show that by applying the semiotic approach new and significant meaning constellations can be found in the client's change relevant talk during motivational counseling.